2002
DOI: 10.4049/jimmunol.168.3.1226
|View full text |Cite
|
Sign up to set email alerts
|

Viral IFN-Regulatory Factors Inhibit Activation-Induced Cell Death Via Two Positive Regulatory IFN-Regulatory Factor 1-Dependent Domains in the CD95 Ligand Promoter

Abstract: The CD95 (also called APO-1/Fas) system plays a major role in the induction of apoptosis in lymphoid and nonlymphoid tissues. The CD95 ligand (CD95L) is induced in response to a variety of signals, including IFN-γ and TCR/CD3 stimulation. Here we report the identification of two positive regulatory IFN-regulatory factor-dependent domains (PRIDDs) in the CD95L promoter and its 5′ untranslated region, respectively. EMSAs demonstrate specific binding of IFN-γ-induced IFN-regulatory factor 1 (IRF-1) to the PRIDD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 62 publications
3
46
0
1
Order By: Relevance
“…The human inducible nitric oxide synthase (hiNOS), Fas (CD95), and caspase-1 genes encode pro-inflammatory and pro-apoptotic proteins that play essential roles in the innate immune response and the control of cell death. All three are induced by IFN-␥ in STAT1-and IRF-1-dependent fashion (22,26,27). Consistent with its enhancing effect on IRF-1 and STAT1 (Fig.…”
Section: Inhibition Of Mtor Enhances the Induction Of Late Ifn-␥-stimsupporting
confidence: 52%
“…The human inducible nitric oxide synthase (hiNOS), Fas (CD95), and caspase-1 genes encode pro-inflammatory and pro-apoptotic proteins that play essential roles in the innate immune response and the control of cell death. All three are induced by IFN-␥ in STAT1-and IRF-1-dependent fashion (22,26,27). Consistent with its enhancing effect on IRF-1 and STAT1 (Fig.…”
Section: Inhibition Of Mtor Enhances the Induction Of Late Ifn-␥-stimsupporting
confidence: 52%
“…Coimmunoprecipitation studies confirm binding of FADD to caspase-8 (Supplementary Figure S2). Since previous literature (Kirchhoff et al, 2002;Park et al, 2004) and our own studies have suggested involvement of the extrinsic death pathway in IRF-1-induced IRF-1 induces ligand-independent FADD-mediated apoptosis MT Stang et al apoptosis, we expected the involvement of death receptors and ligands. We found, however, that the involvement of FADD and caspase-8 signaling appeared to be independent of classical death-ligands since neutralizing antibodies were ineffective in abrogating IRF-1 induced apoptosis.…”
Section: Discussionmentioning
confidence: 88%
“…1). vIRF-1, encoded by K9, transforms cells in culture, is tumorigenic in nude mice, and inhibits apoptosis induced by Sendai virus infection, IFN-␣, IFN-␤, TNF-␣, TCR/CD3 cross-linking, and p53 (64,160,174,234,258,293,302,369,456,457). It also blocks programmed cell death mediated by cooperation of the cellular protein GRIM19 with IFN-␤ and retinoic acid (456).…”
Section: Lytic Genes and Kshv Pathogenesismentioning
confidence: 99%
“…However, vIRF-1 has been best characterized for inhibiting the transcriptional programs induced by exogenous IFNs (174,293), specifically by blocking transcriptional activation by the cellular proteins IRF-1 and IRF-3. This is mediated by multiple mechanisms, including direct binding of vIRF to its cellular homologs, competitive binding to the transcriptional coactivator p300, and inhibition of the histone acetyltransferase activity of p300 (64,160,258,292,302,550). vIRF-1 also directly binds p53 to inhibit its phosphorylation and acetylation and blocks its ability to transactivate transcription (369,457).…”
Section: Lytic Genes and Kshv Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation